Cotton Picking Bag – Adaptability, Acceptability and Feasibility among Rural Women (Indian Journal of Extension Education, 2017)
Rural women play a pivotal role in Indian agriculture. They perform key agricultural tasks in all regions of the world ranging from hoeing to harvesting, threshing and post harvesting operations. All these activities stretch on throughout the day due to which women work hard for longer hours in the field and at home. Life of women is therefore, full of drudgery and they face a lots of health problems at every moment. Keeping these facts in mind new technology (cotton picking bag) was introduced for cotton pickers to relive from drudgery as well as other health problems. The study was undertaken in four villages namely, Dhandakheri, Dumerkhan, Dhigana and Pandu Pindara of Jind district of Haryana state. The study was conducted on purposively selected samples of 100 rural women respondents (25 from each village) who were actively involved in cotton picking. After getting training 73 to 89 per cent of rural women were highly skilled in drafting, cutting and stitching of cotton picking bag. Regarding overall adoption feasibility, maximum AFI score was 93.46 per cent followed by 88.46 per cent on attributes like practibility and cultural compatibility which indicates high adoption potential of cotton picking bag among rural women.